Integrated approach to accounting in agriculture in the context of sustainable development and circular economy - Maryna Dubinina; Natalia Potryvaieva; Olena Dovgal; Olena Usykova; Vitalii Kuzoma (Наукові горизонти)
The study was conducted to analyse the possibilities of integrating the principles of sustainable development and circular economy into the accounting system of agricultural enterprises. The study employed various methods to analyse the implementation of the circular economy in agricultural enterprises. The study found that the integration of the principles of sustainable development and circular economy into the accounting of agricultural enterprises allows increasing the efficiency of resource management. It was also found that the introduction of environmental and social indicators into the accounting system contributes to better control over the use of natural resources, reduction of production costs, and minimisation of waste. The analysis revealed that the application of the circular model in agriculture contributes to the economic sustainability of enterprises through the reuse of materials and reduced dependence on external resources. It was also confirmed that such innovations positively affect the ecological state of land and other natural resources used in agricultural production. The study found that the use of circular approaches in accounting can increase the transparency and accuracy of financial reports, considering the environmental impact. The analysis of enterprises from different countries, such as Nibulon, The Green Shop, and the Farmers for Climate Action cooperative, revealed concrete benefits of implementing circular approaches in reducing costs, improving resource management, increasing environmental efficiency, and increasing profitability, which confirmed their significance in modern agribusiness. It was established that the assessment of environmental and social factors enables a more objective determination of the economic efficiency of agricultural enterprises. Furthermore, it was proved that the implementation of sustainable approaches reduces the risks associated with environmental regulations and increases the confidence of investors and partners. It was concluded that the integration of these approaches contributes to the long-term sustainability of agricultural enterprises. The study made a valuable contribution to science by revealing innovative approaches to the integration of environmental and social indicators into the accounting of agricultural enterprises, which contributed to their sustainable development and responsibility towards the environment